PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA KARYAWAN PADA PT ERAFONE ARTHA RETAILINDO MAKASSAR - Muhammad Aisyar Mata; Agung Widhi Kurniawan; Zainal Ruma; Chalid Imran Musa; Tenri Sayu Puspitaningsih Dipoatmodjo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The purpose of this study is to test whether the Reward and Punishment variables have an influence on Employee Work Motivation at PT. Erafone Artha Retailindo Makassar. To find out which variable has the most influence on employee motivation. The research was conducted using a survey method, where data was obtained by distributing questionnaires to 55 respondents. The population in this study are all employees at PT. Erafone Artha Retaiindo Makassar, the sampling method used is saturated sample. The collected data were analyzed using multiple linear regression equations. The results of the study show that there is an influence between rewards on employee motivation. Through the results of the calculations that have been carried out, the t value is 7.649 with a significant result of 0.000 <0.05. And the results of testing the hypothesis partially prove the effect of punishment on Employee Motivation. Through the results of the calculations that have been carried out, the t value is 4.836 with a significant result of 0.000 <0.05. This means that there is an influence between reward and punishment variables on employee motivation at PT. Erafone Artha Retailindo Makassar